A nonrandomized phase I and biomarker trial of regorafenib in advanced myeloid malignancies. Issue 2 (6th March 2022) - How, Joan; Ren, Siyang; Lombardi‐Story, Jennifer; Bergeron, Meghan; Foster, Julia; Amrein, Phillip C.; Brunner, Andrew M.; Fathi, Amir T.; Hock, Hanno; Khachatryan, Anna; Kikuchi, Hiroto; Ng, Mei Rosa; et al.
Abstract: We conducted a single‐center, open‐label, dose escalation, and expansion phase I trial of the antiangiogenic multikinase inhibitor regorafenib in patients with advanced myeloid neoplasms. We enrolled 16 patients with relapsed/refractory acute myeloid leukemia (AML), myeloproliferative neoplasms (MPN), chronic myelomonocytic leukemia (CMML), or myelodysplastic syndrome (MDS). A 3 + 3 dose escalation design was used with two planned dose levels (120 or 160 mg daily) and one de‐escalation level (80 mg daily). An additional 10 patients were treated on an expansion cohort. The recommended phase two dose of regorafenib was 160 mg daily, with no dose‐limiting toxicities. The best overall disease response by International Working Group criteria included one partial and stable disease in 11 patients. Tissue studies indicated no change in Ras/mitogen‐activated protein kinase (MAPK) pathway activation in responders. Pharmacodynamic changes in plasma VEGF, PlGF, and sVEGFR2 were detected during treatment. Baseline proinflammatory and angiogenic cytokine levels were not associated with clinical response. Single‐agent regorafenib demonstrated an acceptable safety profile in relapsed/refractory myeloid malignancy patients. Most patients achieved stable disease, with modest improvements in cell counts in some MDS patients. Biomarker studies were consistent with on‐target effects of regorafenib on angiogenesis. Future studies should investigate the role of regorafenib in combination therapy approaches.